2020
DOI: 10.1080/19466315.2019.1700157
|View full text |Cite
|
Sign up to set email alerts
|

A General Framework for Treatment Effect Estimators Considering Patient Adherence

Abstract: Randomized controlled trials remain a gold standard in evaluating the efficacy and safety of a new treatment. Ideally, patients adhere to their treatments for the duration of the study, and the resulting data can be analyzed unambiguously for efficacy and safety outcomes. However, some patients may discontinue the study treatment due to intercurrent events, which leaves missing observations or observations that do not reflect the randomly assigned treatment. Frequently, an intent-to-treat analysis (or a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 39 publications
(43 reference statements)
0
67
0
Order By: Relevance
“…These estimators are consistent for the treatment effect in the adherent strata of interest under some assumptions, and simulations demonstrated that the ACEs provide consistent estimates of the treatment difference for sample sizes that are typical for clinical trials. As the methods are complex and have been previously described, 6 here we only provide a high‐level description of the methods. The following assumptions have been posed for the validity of the ACEs: normalA1:Y=Y()1T+Y()0()1T normalA2:Z=Z()1T+Z()0()1T normalA3:A=A()1T+A()0()1T normalA4:T{},,,,,Y()1A()1Z()1Y()0A()0Z()0X normalA5:A{}i{},,Y()1Y()0Z()1i{},XZ()i,i=0,1 normalA6:Y()iZ()1i{},XZ()i,i=0,1 normalA7:Z()0Z()1X …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…These estimators are consistent for the treatment effect in the adherent strata of interest under some assumptions, and simulations demonstrated that the ACEs provide consistent estimates of the treatment difference for sample sizes that are typical for clinical trials. As the methods are complex and have been previously described, 6 here we only provide a high‐level description of the methods. The following assumptions have been posed for the validity of the ACEs: normalA1:Y=Y()1T+Y()0()1T normalA2:Z=Z()1T+Z()0()1T normalA3:A=A()1T+A()0()1T normalA4:T{},,,,,Y()1A()1Z()1Y()0A()0Z()0X normalA5:A{}i{},,Y()1Y()0Z()1i{},XZ()i,i=0,1 normalA6:Y()iZ()1i{},XZ()i,i=0,1 normalA7:Z()0Z()1X …”
Section: Methodsmentioning
confidence: 99%
“…The φfalse^t()Xj is the expected value of the product of this probability of adherence to the alternative treatment and ϕfalse^t()Xj, conditional on X . Again, the details for the construction of ϕfalse^t,φfalse^t, and hfalse^t have previously been described in detail 6 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations